Phylogenetic analysis of vp2 gene of the infectious bursal disease virus in South China during 2023 - Zhu, Kensi; Wu, Qi; Leng, Mei; Wang, Zhanxin; Lin, Wencheng (Frontiers in Veterinary Science, 2025)
Infectious Bursal Disease (IBD) is an acute, highly infectious, immunosuppressive disease caused by the infectious bursal disease virus (IBDV). To elucidate the prevalence of IBDV in southern China, a total of 60 tissues (including spleen and bursa) suspected of IBDV infection were collected from broiler chickens in 2023. In this study, a total of 31 IBDV strains were successfully isolated. The vp2 gene sequences of these isolates were sequenced and analysed. The results showed that 8 of the isolates were identified as very virulent strains, 11 as classical strains and 12 as novel variants. The nucleotide sequence identity among the isolates ranged from 90.7 to 100%, as determined by MegAlign. Further analysis revealed that the novel mutant strains exhibited characteristic amino acid sites are 252I, 254 N, 262Y, 299S and 318D. Phylogenetic analysis of the IBDV isolates and reference strains from South China demonstrated that the novel mutant strain has diverged from previously prevalent mutant strains, such as Variant E and GLS, forming a distinct lineage. This finding implies that the high mutation rate of IBDV may compromise vaccine efficacy and pose new challenges for the prevention and control of IBDV in poultry production.